A Survey of Knowledge, Attitude and Performance of People of Fasa on Segregation of Household Solid Wastes, Fasa, Iran, 2017 - Mansour Kashfi; Mostafa Eslahi; Tayebeh Rakhshani; Hasan Hashemi; Pejhman Baqeri; Mehdi Sharafi (Shiraz University of Medical Sciences, 2018)
Introduction: Environmental health is definitely one of the issues and challenges considered by human societies on the eve of the third millennium. Therefore, the present study was conducted to determine the knowledge, attitude and performance of the people of Fasa on segregation of municipal solid wastes in 2017. Method: This cross - sectional study was conducted on 400 residents of Fasa who were selected through cluster sampling. The tool used in this study was a Lickert-spectrum questionnaire, which was essentially a combination of two standard instruments and the researcher's field studies. The data were analyzed using the SPSS 22 software as well as descriptive statistics, Man-Whitney test and one - way ANOVA test. Results: The results of this study showed that the mean knowledge, attitude and performance of the people were 23.5±5.3, 13.5±3.0, and 21.5±2.6, respectively. 43.7% of the subjects had weak knowledge (188 people), 28.6% had moderate knowledge (123 people) and 27.7% had good knowledge (119 people). Moreover, 36.6% had weak attitude (156 people), 19.3% had moderate (85 people) and 44% had good attitude (189 people). Finally, the performance of 46% of the participants was weak (198 people), that of 30.5% was moderate (131 people), and 23.5% had good performance (101 people). The mean scores of knowledge, attitude and performance of the male and female subjects were not significantly different.